2020
DOI: 10.1088/1742-6596/1560/1/012075
|View full text |Cite
|
Sign up to set email alerts
|

Application of laser fluorescence spectroscopy in non-invasive assessment of ultraviolet-induced skin immune response in vivo

Abstract: Acute ultraviolet (UV) -induced skin damage is associated with structural alterations, vasodilatation and inflammatory response. Leukocyte infiltration is one of the main features of inflammation and could be found in the area of UV injury. It was shown that porphyrins which have well-known autofluorescent properties play a role in the chemoattraction of immune cells to the area of local damage. This study examined the possibility of application of laser fluorescence spectroscopy (LFS) in the assessment of ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Experiments using the LFS conducted by et al revealed porphyrins' accumulation in the area of artificially induced skin inflammation in Wistar rats [41]. It is important to note that we previously demonstrated that the autofluorescence of porphyrins reflects the severity of inflammatory infiltration in the skin induced by acute UVB exposure [42].…”
Section: Optical Diagnostics Resultsmentioning
confidence: 75%
“…Experiments using the LFS conducted by et al revealed porphyrins' accumulation in the area of artificially induced skin inflammation in Wistar rats [41]. It is important to note that we previously demonstrated that the autofluorescence of porphyrins reflects the severity of inflammatory infiltration in the skin induced by acute UVB exposure [42].…”
Section: Optical Diagnostics Resultsmentioning
confidence: 75%